HEALTH CONDITION OF EXTREMELY LOW BIRTH WEGHT INFANTS - Валентина Ивановна Черняева; Ольга Александровна Зотова; Елена Александровна Шакирова; Наталья Борисовна Колесникова; Александра Сергеевна Чуйкова; Ольга Георгиевна Крючкова (The Publishing House Medicine and Enlightenment, 2019)
Aim - to assess the health status of Extremely Low Birth Weight Infants. Materials and Methods. The retrospective case-control study was conducted. The research included 400 children born in the L.A. Reshetova Regional Clinical Perinatal Center during 2014-2018. Group I (main group) included 200 newborns with extremely low body weight (ELBW), group II (comparison group) included 200 newborns with normal body weight. Results. Newborns with extremely low body weight (ELBW) at birth had significant disturbances in health condition: the hypoxemic damage of the brain (HDB) was diagnosed in 78.0 %, 32.0 % were diagnosed as severe cases, in 33.0 % of cases anemia was diagnosed, in 55.0 % of cases the intrauterine infection (IU) with the damage of central nervous system (encephalomeningitis) was revealed; pre-natal hydrocephaly, retinopathy, rickets were also found. Malformations were diagnosed in 58.0 % of newborns, defects of a cardiovascular system were most common. Conclusion. Health of the children born with ELBW has considerably higher rate of asphyxia, damage of the central nervous system of infectious character, anemia, and malformations of various systems and need the respiratory support due to the respiratory distress syndrome (RDS).